Imbalanced distribution of regulatory T cells and Th17.1 cells in the peripheral blood and BALF of sarcoidosis patients: relationship to disease activity and the fibrotic radiographic phenotype - Zhang, Hui; Jiang, Dingyuan; Zhu, Lili; Zhou, Guowu; Xie, Bingbing; Cui, Ye; Costabel, Ulrich; Dai, Huaping (Frontiers in Immunology, 2023)
Rationale: Sarcoidosis is a granulomatous interstitial lung disease involving a complex interplay among diverse CD4+ T-cell subsets. Originally described as a Th1 inflammatory disease, recent evidence suggests a critical role of both effector and regulatory T-cell subgroups in sarcoidosis, but this remains controversial. Objectives: We aimed to investigate the distribution of CD4+ T-cell subpopulations in sarcoidosis patients and potential associations with clinical disease activity and a radiographic fibrotic phenotype. Methods: We measured the frequencies of regulatory T cells (Tregs), Th1, Th17, and Th17.1 cells in peripheral blood and/or bronchoalveolar lavage fluid (BALF) of 62 sarcoidosis patients, 66 idiopathic pulmonary fibrosis (IPF) patients and 41 healthy volunteers using flow cytometry. We also determined the changes of these T-cell subpopulations in the blood at follow-up visits of 11 sarcoidosis patients. Measurements and Results: An increased percentage of Tregs was observed in peripheral blood of sarcoidosis patients, with a positive association to disease activity and a fibrotic radiographic phenotype. We found a higher frequency of Tregs, a lower proportion of Th17.1 cells and a lower ratio of Th17.1 cells to total Tregs in the peripheral blood of either active or fibrotic sarcoidosis patients, compared to IPF patients or healthy donors. To the contrary, a lower frequency of Tregs and a greater proportion of Th17.1 cells was found in BALF of sarcoidosis patients, in comparison with IPF patients. There was an imbalance of Tregs and Th17.1 cells between peripheral blood and BALF in sarcoidosis patients. Following immunoregulatory therapy, the proportion of circulating Tregs of sarcoidosis patients decreased. Conclusions: Higher Tregs proportion in peripheral blood of sarcoidosis patients was related to disease activity, fibrosing phenotype and need for immunoregulatory therapy. The imbalanced distribution of Tregs and Th17.1 cells in peripheral blood and BALF suggests an effect of the lung microenvironment on the immunological pathogenesis of sarcoidosis. Further studies on functional analysis of Tregs and Th17.1 cells in sarcoidosis are warranted.